Labour Arbitration Procedures - Chartier, Roger (Relations industrielles / Industrial Relations, 1957)
The article reviews the book, "Labour Arbitration Procedures," by C. H. Curtis. Published by the Department of Industrial Relations, Queen's University (90 pages).